Pengaruh Stretching Exercise terhadap Perubahan Kekuatan Otot pada Pasien Pasca Stroke - Ria Ika Imelda; Enni Mulyatsih; Wilhelmus Hary Susilo (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2020)
Stroke is a functional brain disorder in the form of nerve paralysis / neurological deficits due to impaired blood flow in one part of the brain. Stroke patients will experience hemiparese resulting in decreased muscle strength. Stretching Exercise is one of the stretching exercises that serves to increase muscle strength. The purpose of this study was to determine the effect of stretching exercise on changes in muscle strength in post-stroke patients in outpatient hospitals. Jakarta National Brain Center. This research is a quasi experimental design study with a randomized pretest-posttest control group approach. The number of samples in this study were 109 respondents who were divided into intervention groups of 82 respondents who were given stretching exercises 3 times a week for 10 weeks and the control group of 27 respondents using the Wilcoxon and Mann Whitney Tests. The results showed that muscle strength increased significantly after stretching exercises (Ï value = 0.000). Conclusion, Stretching Exercise affects the increase in muscle strength of post-stroke patients in the outpatients of the Jakarta National Brain Center Hospital. Suggestions, the results of this study can contribute knowledge related to independent interventions namely Stretching Exercise for post-stroke patients who experience physical weakness.Â Keywords :Stroke, Hemiparese, Stretching Exercise, Muscle Strength